REDUCE PRODUCTION COST IN TEXTILE INDUSTRY BY PAYBACK ANALYSIS METHOD - Singh, Er.Avtar (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
The main conclusions of my paper are save the money by replacing by energy efficient motor to improve the losses, power factor, maintenance and life of the motor. The purpose of the paper is to perform an introductory investigation of replacing energy efficiency motor by standard induction motor with the help of a case study in textile industry. These are done by calculation comparison data between energy efficiency motor and standard induction motor.